Diagnosis and treatment of ejaculatory duct obstructions - Firdolas, Fatih; Orhan, Irfan (Aves, 2010)
Ejaculatory duct pathologies which are determined in approximately 5% of infertile men can be evaluated in two different forms, either as congenital or acquired. Congenital pathologies include midline or lateral cysts, atresia and stenosis of ejaculatory ducts, whereas acquired pathologies develop due to stones or calcifications following an infection, surgery or urethral interventions. Recently used novel diagnostic techniques have revealed that distal ejaculatory duct pathologies are more frequent than expected. Semen analysis is of importance in the diagnosis of ejaculatory duct obstruction that has no pathognomonic finding in the physical examination. Azoospermia with a low volume and acidic semen is characteristic, especially in complete obstructions. Semen parameters may vary in a broad range from azoospermia to normozoospermia in partial and functional ejaculatory duct obstructions. Historically, vasography has been used as the gold standard method in the diagnosis of ejaculatory duct obstruction. However, transrectal ultrasonography (TRUS) is the currently preferred imaging method, since it can be performed with ease and has several advantages. But, the gold standard diagnostic method for ejaculatory duct obstruction, which is one of the correctable causes of male infertility, has not been defined yet. Thus, efforts to define new diagnostic methods and develop less invasive treatment models for this pathology are current research topics in urology. The standard treatment of ejaculatory duct pathologies is transurethral resection of ejaculatory duct (TUR-ED). An effective treatment method for the pathologies that impair the peristaltism and lead to atonic obstruction in the male reproductive ejection ducts which eventually cause partial and functional obstruction of the ejaculatory ducts has not been defined yet. It would be possible to treat many idiopathic infertility pathologies, with novel and effective treatment methods for this kind of pathologies.
Ejakülatör kanal obstrüksiyonlarının tanı ve tedavisi
Keywords: Ejaculatory duct; obstruction; diagnosis; treatment